Maternal catalase supplementation regulates fatty acid metabolism and antioxidant ability of lactating sows and their offspring - Zhou, Tiantian; Cheng, Bei; Gao, Lumin; Ren, Fengyun; Guo, Guanglun; Wassie, Teketay; Wu, Xin (Frontiers in Veterinary Science, 2022)
Sows are susceptible to oxidative stress, which negatively affects the growth and development of their offspring, especially lipid metabolism. The current study was aimed to investigate the effects of maternal catalase (CAT) supplementation from late gestation to lactation day 14 on antioxidant ability and fatty acids metabolism with regard to the sow-piglet-axis, which has rarely been reported before. Results showed that lactating sows in the CAT group could produce more milk, had significant increased antioxidant enzymes activity, lower content of serum LDL and significantly decreased plasma C18:3n3 content. What’s more, maternal CAT supplementation improved BWd14 and ADG (P<0.05), and increased the antioxidant ability as evidenced by increased related enzymes activity and changed genes expression level. It significantly affected lipid metabolism of suckling piglets manifested by increasing the serum ALT, CHOL, and LDL (P<0.05) level and modulating plasma medium- and long-chain fatty acids (SCFAs), as well as regulating the genes expression involved in lipid metabolism. In conclusion, maternal CAT supplementation could regulate the fatty acid composition and enhance the antioxidant ability of sows and offspring during the lactating period and further promote the growth of suckling piglets. These findings might provide a reference value for the utilization of CAT as supplement for mother from late pregnancy to lactation period to promote the fatty acid metabolism of offspring.